2022
DOI: 10.1002/smtd.202200269
|View full text |Cite
|
Sign up to set email alerts
|

Freestanding Helical Nanostructured Chiro‐Photonic Crystal Film and Anticounterfeiting Label Enabled by a Cholesterol‐Grafted Light‐Driven Molecular Motor

Abstract: Design and fabrication of freestanding chiro‐photonic crystal film with the ability to change color over the whole visible light spectrum is appealing for anticounterfeiting technology and smart labels. Utilizing a newly synthesized light‐responsive molecular motor functionalized with cholesterol (chol‐MM) on the rotor, novel light‐controlled photonic crystal is prepared by doping the novel chol‐MM into liquid crystals (LCs). Thanks to the liquid crystalline cholesterol substituent, the chol‐MM can be triggere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 33 publications
0
40
0
Order By: Relevance
“…Very recently, our group extent this work by doping a cholesterol-grafted OAMM into a thermochromic LC matrix. [61] The reflective band of prepared CLC changed over the whole visible range by visible light exposure and heating, enabling the preparation of freestanding optical labels.…”
Section: Dynamic Photonic Crystals With Tunable Bandgapmentioning
confidence: 99%
“…Very recently, our group extent this work by doping a cholesterol-grafted OAMM into a thermochromic LC matrix. [61] The reflective band of prepared CLC changed over the whole visible range by visible light exposure and heating, enabling the preparation of freestanding optical labels.…”
Section: Dynamic Photonic Crystals With Tunable Bandgapmentioning
confidence: 99%
“…The PSCLC films can be used as sensors for temperature, humidity, and chemicals . Recent results indicated that they could be used for programmable paintings, , colorful-patterned CLC materials, , and rewritable papers …”
Section: Introductionmentioning
confidence: 99%
“…The PSCLC films can be used as sensors for temperature, 28 humidity, 29 and chemicals. 30 Recent results indicated that they could be used for programmable paintings, 31,32 colorful-patterned CLC materials, 33,34 and rewritable papers. 35 To tune the structural color of PSCLC films, both phase separation 36 and chemical injection techniques 37,38 were developed.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by this, researchers proposed the concept of photonic crystals to simulate such structural colors. The structural colors produced by the reflection of photonic crystals are highly saturated and resistant to fading. , Cholesteric liquid crystals (CLCs) are widely used to fabricate structural color materials with specific patterns and dynamic responses, which can be formed by adding a chiral dopant to achiral nematic LCs . The supramolecular helical structure in CLC results in a selective circular polarization reflection on light, also known as Bragg reflection.…”
Section: Introductionmentioning
confidence: 99%